(untitled) (Economics and region, 2025)
The article presents the state conceptual model of digital traceability «Trek.Food», which integrates the platforms «Diia.Business», «Diia.Inspector» and QR-identification tools into a unified control ecosystem. A digital verification architecture for production and storage facilities has been developed, enabling real-time audits of compliance with HACCP standards, supported by risk-based regulatory analytics. Mechanisms for dynamic QR safety certificates have been introduced as digital passports for product batches, shifting the focus of state control from the business entity to each specific product batch. A methodology of cyclical digital oversight is proposed, enabling automatic inspections and corrective actions through a single digital environment triggered by electronic transactions or consumer QR-code scans, thus enhancing accountability across supply chains. The model reduces regulatory burden, minimizes the need for physical inspections, increases transparency, and builds consumer trust in online food sales. The integration of staff digital competencies and the implementation of a reputational monitoring system further promote voluntary compliance with safety standards. Ultimately, the model ensures flexible state oversight and facilitates simplified access for small food businesses to online markets.